Analisis Indeks Massa Tubuh dan Kondisi Fisik Atlet Floorball Kota Surabaya - Andreanto, Mochamat Rizal; Hariyanto, Agus (Faculty of Sport and Health Sciences, 2021)
Physical condition is needed to improve physical ability to perform certain tasks, without fatigue. The purpose of this study was to analyze the anthropometry and physical condition of floorball athletes in the city of Surabaya. This study uses a quantitative descriptive approach. The sample in this study were 20 males floorball athletes in the city of Surabaya. The variables analyzed in this study are anthropometry and physical conditions which include agility, speed, endurance and power. The results showed that the average weight of the athletes was 59.35 ± 12.04 kg. The average height of the athletes was 1.69 ± 0.06 m, the average BMI of the athletes was 20.74 ± 3.99. The results of physical condition analysis showed that majority of athletes had agility and speed in the less category, which were 65% and 55% respectively. In term of endurance and power, it was found that 55% of endurance and power level of floorball athletes fell into sufficient category. Thus, the results of the research on floorball athletes in the city of Surabaya should be of special concern to coaches to improve the physical condition of athletes by providing structured and appropriate training programs in order to obtain better results.